Identification of Mathematical Resilience Based Student Brain Dominance - Bayu Sukmaangara (PT Ilmu Inovasi Nusantara, 2025)
Differences in students' resilience levels are very important, especially when facing difficulties in solving problems. The relationship between brain dominance and mathematical resilience, as well as the different ways of thinking of the two hemispheres of the brain, requires research on mathematical resilience based on brain dominance. In addition, research on mathematical resilienci based on brain dominance has not been conducted. The purpose of this study was to obtain a picture of mathematical resilience in terms of brain dominance. The research method used was qualitative with a descriptive exploratory approach. The instruments used were a mathematical resilience questionnaire, a brain dominance test, and an unstructured interview. The subject of this study were 3 subjects who met the criteria consisting of 1 subject with left brain dominance, 1 subject with balanced brain dominance, and 1 subject with right brain dominance. The results of the mathematical resilience study based on brain dominance were that left brain dominance students met all the measured indicators, balanced brain dominance students met 4 measured aspects and 2 aspects were not met, and right brain dominance students met all measured indicators.